TRAFFICKING AND PROSTITUTION OF BRAZILIAN WOMEN IN PORTUGAL: the journalistic discourse between the stereotyping and the victimization - Minga, Ester Amaral de Paula (Brazilian journalism research, 2020)
In the beginning of this century, the human trafficking received wide attention in Portugal, which developed several actions to reinforce the legislation in this area. Not by coincidence, this attention is contemporary with the consolidation of the country as a receiver place, which indicates its inextricable relation with migration phenomenon. In this article, we purpose to analyze the representation of human trafficking for sexual exploitation – one of the most prominent vectors of this criminal practice –, in the journalistic discourse about Brazilian women immigrant’s prostitution. However, the Brazilian woman’s image that emerged in the news about prostitution, following the “Mothers of Bragança” case, in 2003, privileged the stereotyping, put in the background issues about trafficking and exploitation (Correia, 2014). Analyzing some texts of Público and Expresso newspapers published during these years, we observe an erratic route which sometimes privileges a sensational tone, and sometimes pay attention to the exploitation and trafficking issues, reflecting in this way the inconsistency found in the law about the theme. No início deste século, a problemática do tráfico de pessoas recebeu ampla atenção em Portugal, que empreendeu sucessivas ações de reforço legislativo neste âmbito. Não por acaso, esta atenção é contemporânea à consolidação do país como local de acolhimento, o que indica sua relação inextricável com o fenômeno migratório. Neste artigo, propomo-nos a analisar a representação do tráfico de pessoas para fins de exploração sexual – um dos vetores mais pronunciados desta prática –, a partir do discurso jornalístico sobre a prostituição de imigrantes brasileiras. Todavia, a imagem da brasileira que emergiu das reportagens sobre prostituição, em seguimento ao caso “Mães de Bragança”, em 2003, privilegiou a estereotipização, pondo em segundo plano a questão do tráfico e da exploração (Correia, 2014). A partir da análise a algumas peças dos jornais Público e Expresso ao longo destes anos, observamos um percurso errático em que ora se privilegia a linguagem sensacionalista, ora se enfoca a questão da exploração e do tráfico, refletindo assim a inconsistência verificada na legislação devotada ao tema. A principios de este siglo, el problema de la trata de personas ha recibido amplia atención en Portugal, que libró sucesivas acciones de fortalecimiento legislativo en la materia. No por casualidad, esta atención es contemporánea a la consolidación del país como lugar de acogida, lo que indica su relación inextricable con el fenómeno migratorio. En este artículo nos proponemos analizar la representación del tráfico de personas con fines de explotación sexual – uno de los vectores más pronunciados de esta práctica –, a partir del discurso periodístico sobre la prostitución de inmigrantes brasileñas. Sin embargo, la imagen de la brasileña que emergió de los reportajes sobre prostitución, en seguimiento al caso “Madres de Bragança”, en 2003, privilegió la estereotipización, poniendo en segundo plano la cuestión del tráfico y de la explotación (Correia, 2014). A partir del análisis a algunos textos de los periódicos Público y Expresso a lo largo de estos años, observamos una ruta errática en que por veces se privilegia el lenguaje sensacionalista y por veces se enfoca la cuestión de la explotación y del tráfico, reflejando así la inconsistencia verificada en la legislación dedicada al tema.